Rapid DOTS expansion in India - Khatri G.R.; Frieden Thomas R. (Bulletin of the World Health Organization, 2002)
Since late 1998 the coverage of the DOTS strategy in India has been expanded rapidly. In both 2000 and 2001 the country probably accounted for more than half the global increase in the number of patients treated under DOTS and by early 2002 more than a million patients were being treated in this way in India. As a result, nearly 200 000 lives were saved. The lessons learnt relate to the importance of the following elements of the programme: (1) getting the science right and ensuring technical excellence; (2) building commitment and ensuring the provision of funds and flexibility in their utilization; (3) maintaining focus and priorities; (4) systematically appraising each area before starting service delivery; (5) ensuring an uninterrupted drug supply; (6) strengthening the established infrastructure and providing support for staff; (7) supporting the infrastructure required in urban areas; (8) ensuring full-time independent technical support and supervision, particularly during the initial phases of implementation; (9) monitoring intensively and giving timely feedback; and (10) continuous supervision. Tuberculosis (TB) control still faces major challenges in India. To reach its potential, the control programme needs to: continue to expand so as to cover the remaining half of the country, much of which has a weaker health infrastructure than the areas already covered; increase its reach in the areas already covered so that a greater proportion of patients is treated; ensure sustainability; improve the patient-friendliness of services; confront TB associated with human immunodeficiency virus (HIV) infection. It is expected that HIV will increase the number of TB cases by at least 10% and by a considerably higher percentage if HIV becomes much more widespread. India's experience shows that DOTS can achieve high case-detection and cure rates even with imperfect technology and often with an inadequate public health infrastructure. However, this can only happen if the delivery programme is appropriately designed and effectively managed.